Analysis of Computational Thinking Skills of Students on Exponential Equation Materials through Learning Videos - Mulyono, Budi; Hapizah, Hapizah; Fitrisyah, Muhammad Aidil (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
Computational Thinking (CT) is a very important skill for everyone because it is not only for solving problems related to computer science and mathematics, but also for solving various problems in everyday life. The application of computational thinking skills in Indonesia is still constrained which results in low computational thinking skills of students. This study aims to identify the ability of computational thinking in students through learning videos containing problem solving using the stages of computational thinking developed on the material of exponential equations. This study used descriptive qualitative methodology with 34 grade 10 learners in one of the high schools in Palembang as research subjects, focusing on three learners who showed high, medium, and low abilities. The research was conducted in three stages: preparation, implementation, and data analysis. Data were collected through written tests and interviews to measure learners' computational thinking ability. The results were analyzed through three stages, namely: data reduction, data presentation, and conclusion drawing. The results showed that learners showed proficiency in exponential material, especially in terms of pattern recognition and abstraction. However, in decomposition and algorithm skills, learners show a lack of ability in solving problems with a systematic approach and accurate solutions.